2014
DOI: 10.1021/jp508006s
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)-Induced Activation of Chloride and Bromide from Modeled Salt Pans

Abstract: The photochemistry of halides in sea spray aerosol, on salt pans, and on other salty surfaces leads to a formation of reactive halogen species. We investigated the photochemical formation of atomic chlorine (Cl) and bromine (Br) in the gas phase in the presence of laboratory-modeled salt pans consisting of sodium chloride doped with iron(III) chloride hexahydrate (0.5 and 2 wt %). The samples were spread on a Teflon sheet and exposed to simulated sunlight in a Teflon smog chamber in purified, humidified air in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 98 publications
1
46
0
Order By: Relevance
“…The ISA-induced increase in q Br concentration at seasalt-containing tropospheric conditions has been confirmed (Wittmer et al, 2015b). This establishes ISA as part of an ozone-depleting reaction cycle and additional cooling stage.…”
Section: Tropospheric Ozone Depletion By Isamentioning
confidence: 67%
See 2 more Smart Citations
“…The ISA-induced increase in q Br concentration at seasalt-containing tropospheric conditions has been confirmed (Wittmer et al, 2015b). This establishes ISA as part of an ozone-depleting reaction cycle and additional cooling stage.…”
Section: Tropospheric Ozone Depletion By Isamentioning
confidence: 67%
“…Dorfman et al (2015) found recent loess dust sedimentation rates in the Alaskan Arctic Burial Lake of 0.15 mm yr −1 . According to research results from artificial iron-doped salt pans (Wittmer et al, 2015b), iron-salt-doped sea-salt aerosols (Wittmer et al, 2015a) or sea-salt-doped iron oxide aerosols or pure iron oxide aerosols in contact with gaseous HCl chloride and bromide in sunlit surfaces are oxidized to q Cl and q Br by photoreduced Fe(III) if the pH of the reaction media is 3.5 or lower.…”
Section: Oxidation Of Ch 4 and Other Ghgs By Sunlit Solid Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, hypersaline environments, such as the Dead Sea or Australian salt lakes, [14] offer conditions that promote iron-induced halogen release, as recently investigated by Wittmer et al for modelled salt surfaces. [15] The present study, however, concentrates on the effect of Fe 3þ in saline aerosols that can also be found in these regions and when mineral aerosol particles mix with sea salt. In particular, chloride (Cl À ) enhances the dissolution of iron.…”
Section: Introductionmentioning
confidence: 96%
“…A more detailed summary and description of Fe III -induced Cl 2 formation can be found in Lim et al [24] or Wittmer et al [15] In addition to the photosensitive iron-induced halogen release mechanism, further trace gas species, such as O 3 , NO x and sulfur dioxide (SO 2 ), possibly influence Cl 2 release, mainly when dissolved in the aqueous phase where they can change the pH, [25] coordinate with Fe 2þ or Fe 3þ , [26] scavenge Cl [22] or additionally activate halides by the known heterogeneous mechanisms. [13] Concerning O 3 , Sadanaga et al [27] observed an enhancement of the O 3 uptake rate and Cl 2 release in the presence of water-soluble Fe 3þ and O 3 in the dark.…”
Section: Introductionmentioning
confidence: 99%